A comparison of preschool and elementary school children learning computer science concepts through a multilanguage robot programming platform - Martínez, Cecilia; Gómez, Marcos J.; Benotti, Luciana (2021)
Fil: Gómez, Marcos J. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.